Fungsi Dewan Perwakilan Rakyat Daerah dalam Penanganan Pandemi Corona Virus Disease 2019: (Studi Undang-Undang Nomor 6 Tahun 2018 tentang Kekarantinaan Kesehatan) - Melta Setya Rahayu Pujianti (Jurnal Hukum Lex Generalis, 2020)
The State of Indonesia is a country that is in the area of intersection between disasters, intercontinental, intercultural, between economic forces, even between civilities that result in the emergence of potential disasters and extraordinary events or known as Emergencies (State Emergency). Therefore, the device of legislation in normal circumstances is not compatible when applied under abnormal circumstances because generally abnormal circumstances are unpredictable. In Indonesia, the constitutional basis for implementing the Emergency Law is stipulated in Article 12 of the 1945 Constitution. Unfortunately, Article 12 of the 1945 Constitution is only once referred to in the laws and regulations labeled "emergency" and the rest do not refer, including Law No. 6 of 2018 on Health Quarantine. In fact, Article 12 of the 1945 Constitution became the legitimacy to apply the laws and regulations extraordinarily. By not referring to Law No. 6 of 2018 to Article 12 of the 1945 Constitution, then ideally Law No. 6 of 2018 is an ordinary legal regime. However, looking at the formulation of Articles 4 and 10 paragraph (1) contains the meaning that Law No. 6 of 2018 runs as an Emergency Law. Anomalies arise on the one hand of Law No. 6 of 2018 is a common law, but applied in emergencies. This is what the author tried to take issue with in the quarantine of health in the area. With anomalies in Law No. 6 of 2018, the implementation of the State of Emergency is in the domain of the Local Government and does not involve the Regional House of Representatives (DPRD). Whereas in handling emergencies many intersect with the function of the DPRD.